Minimally invasive thoracic surgery: robot-assisted versus video-assisted thoracoscopic surgery - Liping Zeng; Tianyu He; Jian Hu (Videosurgery and Other Miniinvasive Techniques)
Minimally invasive techniques have been widely applied in general thoracic surgery. Compared with video-assisted thoracoscopic surgery (VATS), due to its theoretic superiority, robotic surgery is challenging the traditional position of VATS. With its unique advantages, including 3D vision and a high-freedom endowrist, it leads to easier lymph node dissection, more convenient blood vessel dissection, a shorter learning curve and competence for the completion of complex surgery. However, as a new surgical technology, the safety and efficacy of robotic-assisted thoracoscopic surgery (RATS) still need to be further verified. Thus, in this article, we review and summarize the application of RATS versus VATS in general thoracic surgery.